(untitled) (Journal of Laboratory Animal Science, 2019)
As biomedical research becomes more globalized, India can provide the rest of the world possibly unique insights into the care and use of laboratory animals. Nowhere else is such a rich and deep cultural veneration for life juxtaposed with society and technology modernizing at such astonishing speed. How will our Indian colleagues reconcile these two powerful and seemingly contradictory elements? Just as important, will India’s scientific community and regulators regard Western standards of lab animal care as something to adopt in an identical fashion or something to adapt to domestic circumstances? The intent of this address is to explore these fascinating aspects of India today from an outsider’s perspective and to consider how all parties may benefit together.